FRI0364 T REGULATORY CELLS AS BIOMARKER OF DISEASE ACTIVITY AND RESPONSE IN PSORIATIC ARTHRITIS PATIENTS: RESULTS FROM APREMILAST-TREATED COHORT. (June 2019) - Ceccarelli, Fulvia; Pacella, Ilenia; Lucchetti, Ramona; Forniti, Arianna; Spinelli, Francesca; Cipriano, Enrica; Perricone, Carlo; Truglia, Simona; Miranda, Francesca; Scrivo, Rossana; Alessandri, Cristiano; Barnaba, Vincenzo; et al.
Abstract : Background: The PDE4-inhibitor apremilast has been recently introduced in the treatment of Psoriatic Arthritis (PsA). It acts by down-regulating intracellular inflammatory mediators synthesis by elevating cAMP levels. Tregs, a subset of FOXP3+ CD4 T cells, play a key role in preventing immune responses and could exert their suppressive function via cAMP (1). Reduced frequencies of circulating Tregs have been observed in inflammatory disorders, nonetheless very few data are available on PsA patients. Objectives: We evaluated peripheral Tregs in a cohort of PsA patients treated by apremilast. Methods: Seventeen PsA patients (M/F 3/14; median age 56.0 years, IQR 20.0; median disease duration 15.0 years, IQR 11.0) with polyarticular subset treated by apremilast, were evaluated at baseline (T0) and after 6 (T1) and 12 weeks (T1). Clinimetric evaluation included DAS28, DAPSA, CDAI, and SDAI. Moreover, US assessment was performed at wrists, metacarpophalangeal (MCP), and proximal interphalangeal (PIP) joints: synovial effusion/hypertrophy and power Doppler were scored by a semi-quantitative scale (0-3), obtaining a total score (0-198). Treg frequency was assessed in peripheral blood mononuclear cells by flow cytometry, as the percentage of CD127low FOXP3+ in live CD4+ T cells (%Treg). Results: At baseline we identified a median%Tregs of 4.6 (IQR 1.1), inversely correlating with DAS28 (r=-0.5, p=0.02), DAPSA (r=-0.7, p=0.003), CDAI (r=-0.6, p=0.01), SDAI (r=-0.6, p=0.003 and US inflammatory score (r=-0.6, p=0.01) (Figure 1 ). Treatment with apremilast was able to induce a significant improvement in all activity indices at T1 (DAS28, P=0.009; DAPSA, P=0.01; CDAI, P=0.005; SDAI, P=0.006; US score, P<0.0001) and T2 (DAS28, P<0.0001; DAPSA, P=0.007; CDAI, P=0.008; SDAI, P=0.006; US score, P=0.0005). Furthermore, responding patients according with EULAR criteria at T2 showed significantly higher%Treg at baseline in comparison with non-responder patients (median 4.8, IQR 1.2 versus median 2.9, IQR 1.1; P=0.02). Conclusion: The results of our study demonstrate that%Treg is a marker of disease activity in PsA patients. Moreover, the baseline value of Tregs could predict the response to apremilast after 12 weeks of treatment. Reference: [1] Chavele KMet al, FEBS Lett2011. Disclosure of Interests: Fulvia Ceccarelli: None declared, Ilenia Pacella: None declared, Ramona Lucchetti: None declared, Arianna Forniti: None declared, francesca spinelli: None declared, enrica cipriano: None declared, Carlo Perricone Speakers bureau: BMS; Lilly, Celgene, Sanofi, Simona Truglia: None declared, Francesca Miranda: None declared, Rossana Scrivo: None declared, cristiano alessandri: None declared, Vincenzo Barnaba: None declared, Guido Valesini: None declared, Silvia Piconese: None declared, fabrizio conti: None declared